Integrated effect of bio-slurry with chemical fertilizers on the performance of mustard varieties - Pal, Chandona Rani; Paul, Swapan Kumar; Ahmed, Md Towkir; Uddin , Md Romij; Sarker, Uttam Kumer (Research in Agriculture Livestock and Fisheries, 2024)
To assess the importance of bio-slurry in combination with chemical fertilizers on the yield of mustard, a field experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University (BAU), Mymensingh. Four varieties of mustard (BARI sarisha-14, BARI sarisha-11, BARI sarisha-13, Tori-7) along with four fertilizers treatments i.e. control, recommended dose of inorganic fertilizer, bio-slurry @ 5 t ha-1 + inorganic fertilizer, farmers’ practice (average of 15 farmers) was included in this study. The experiment was set up employing randomized complete block design with three replications. The result revealed significant varietal effects on all the yield and yield contributing characteristics. BARI sarisha-13 exhibited the highest seed yield (2.37 t ha-1), which can be attributed to increased branches plant-1, siliqua plant-1 and seeds siliqua-1. Fertilizer treatments significantly affected different yield parameters and yield. Among them, bio-slurry @ 5 t ha-1 + inorganic fertilizer produced the highest seed yield (1.83 t ha-1), while the control yielded the lowest (1.63 t ha-1). The integrated effect of varieties and fertilizers showed promising results. BARI sarisha-13 with bio-slurry @ 5 t ha-1 + inorganic fertilizer produced the highest seed yield (2.56 t ha-1). Therefore, it could be concluded that BARI sarisha-13 with bio-slurry @ 5 t ha-1 + inorganic fertilizer has the potential for maximizing mustard yield. Res. Agric. Livest. Fish. Vol. 11, No. 2, August 2024: 149-157